2017
DOI: 10.1016/j.carj.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Brain Diffusion Changes in Polycystic Ovary Syndrome

Abstract: Polycystic ovary syndrome (PCOS) is the most frequent endocrine disorder in women of reproductive age, affecting 4%-10% of the population. It is a complex disorder classically characterized by chronic oligo-or anovulation, polycystic ovaries, and hyperandrogenism. It is also associated with a number of comorbid conditions, including type 2 diabetes, cardiovascular disease, dyslipidemia, obesity, infertility, and breast and endometrial cancer [1,2].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Other imaging studies showed specific alterations in the white matter (WM) in several brain districts [ 128 , 129 ]. In a pioneer study, Udiavar and colleagues found decreased mean diffusivity at the level of the genu of the corpus callosum and right cingulum [ 110 ].…”
Section: Methodsmentioning
confidence: 99%
“…Other imaging studies showed specific alterations in the white matter (WM) in several brain districts [ 128 , 129 ]. In a pioneer study, Udiavar and colleagues found decreased mean diffusivity at the level of the genu of the corpus callosum and right cingulum [ 110 ].…”
Section: Methodsmentioning
confidence: 99%